Environmental Accountability or Symbolic Reporting? and Evidence from ESG Disclosures in Indonesia’s Telecommunications Industry - Evy Steelyana; Ghassani Ghassani; Fransiska Priska; Kireyna Tamardandika; Michael Dimas Prasetyo (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
This study examines the credibility of Environmental, Social, and Governance (ESG) environmental disclosures by evaluating whether reported sustainability information reflects actual environmental performance in Indonesian telecommunications companies. Using qualitative content analysis of sustainability reports from major telecom firms between 2022 and 2024, the study assesses disclosure transparency, availability of quantitative indicators, and alignment between narrative reporting and measurable outcomes. The findings reveal substantial discrepancies between disclosed commitments and verifiable performance evidence. Although all companies report environmental initiatives, the majority of disclosures are narrative-driven and lack quantitative indicators that enable objective performance assessment. Paper reduction initiatives associated with digitalization provide the most consistent measurable outcomes, while programs addressing electronic waste, recycling, and environmental awareness are typically reported without clear metrics. These patterns suggest that ESG reporting may function not only as an accountability mechanism but also as alegitimacy tool aimed at maintaining stakeholder confidence. From a sustainability accounting perspective, the results highlight a gap between disclosure volume and information reliability. The absence of standardized metrics limits comparability across firms and reduces the decision usefulness of ESG information for investors and regulators. The study also indicates that initiatives integrated into core business operations are more likely to produce measurable outcomes and credible disclosures. This research contributes to sustainability accounting literature by shifting the focus from the existence of environmental programs to the quality and credibility of ESG disclosures. The findings provide implications for regulators, standard-setting bodies, and corporate managers seeking to enhance transparency, accountability, and the effectiveness of sustainability reporting in infrastructure-intensive industries.